PERANAN PENGENDALIAN INTERNAL TERHADAP EFEKTIFITAS PENAGIHAN PIUTANG PADA UMKM SENTRA KAOS SURAPATI BANDUNG: PERANAN PENGENDALIAN INTERNAL TERHADAP EFEKTIFITAS PENAGIHAN PIUTANG PADA UMKM SENTRA KAOS SURAPATI BANDUNG - Kamalah Saadah; Arie Apriadi Nugraha (Jurnal Akuntansi Bisnis dan Ekonomi, 2020)
The implementation of internal controls on receivables collection that is implemented effectively will affect the success of a company in implementing the policy of selling goods or services on credit. This study aims to determine how the role of internal control on the effectiveness of collection of accounts receivable at UMKM Sentra Kaos Surapati Bandung. The factors tested in this study are the internal control of accounts receivable as an independent variable and the effectiveness of collection of accounts as the dependent variable. The research method used in this research is descriptive qualitative